Influence of the Empty Space and the Internal Stresses on the Dielectric Strength in Two-Phase Polymer - Lambri, Osvaldo Agustin F. (2013)
In the present work, a study on the dependence of the Dielectric Strength (DS) as a function of the empty space and the internal stresses into polymer samples has been performed. The empty space was measured by means of positron annihilation lifetime spectroscopy. The internal stresses into the polymer matrix, due to the appearance of the crystalline zones, were determined by applying the inclusion theory results to the dynamic mechanical analysis measurements. Attention to the effect of the chain movement on the electrical breakdown process has been paid. The study has been performed at a mesoscopic scale with the aim of demonstrating the influence of the thermal, mechanical or electrical stresses on the chains movement and their effect on the dielectric breakdown phenomenon. It has been verified that, DS is a function of the empty space into the sample and also of the internal stresses acting at the polymer chains, which result from the crystalline state promoted by chemicrystallization. The empty space decrease and the internal stresses act overlapped against the electrical force operating on the polymer chains. It is deduced from the work, that the precursor phenomenon for the electrical breakdown is the bend of polymer chains, prior to the onset of their collective movement promoted by the electrical forces.